2018
DOI: 10.1103/physrevb.98.155303
|View full text |Cite
|
Sign up to set email alerts
|

Dark-bright exciton coupling in asymmetric quantum dots

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…The optical activity of the dark spin configuration exciton results from the low C s symmetry of the QD confinement potential [9,28,29]. This symmetry breaking is taken into account in the effective Hamiltonian by adding new contributions toĤ eeh in Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical activity of the dark spin configuration exciton results from the low C s symmetry of the QD confinement potential [9,28,29]. This symmetry breaking is taken into account in the effective Hamiltonian by adding new contributions toĤ eeh in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…This symmetry breaking is taken into account in the effective Hamiltonian by adding new contributions toĤ eeh in Eq. (1) [9,28] as…”
Section: Methodsmentioning
confidence: 99%
“…This requires a strong reduction of the symmetry to C s symmetry, for which the twofold rotational invariance is lost, while only a single mirror symmetry containing the growth axis remains [16]. The dark-bright mixing Hamiltonian can be rewritten as [17,18]…”
Section: A General Considerationsmentioning
confidence: 99%
“…where | ± 1 = |s e z = ∓1/2; 3/2, ±3/2 and | ± 2 = |s e z = ±1/2; 3/2, ±3/2 . In the framework of the effective-mass approximation and only taking into account Coulomb correlations for the lower-energy single-particle states, we have previously shown that the amplitudes of the dark-bright exciton mixing terms 11 and 12 are proportional to the magnitude of the VBM parameter γ [17]. We have also studied the effect of the dark-bright exciton coupling on excited multicharged excitonic complexes whose dark spin configurations have shown a detectable level of absorption [19].…”
Section: A General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation